2013
DOI: 10.1371/journal.pone.0058801
|View full text |Cite
|
Sign up to set email alerts
|

Navigational Efficiency of Nocturnal Myrmecia Ants Suffers at Low Light Levels

Abstract: Insects face the challenge of navigating to specific goals in both bright sun-lit and dim-lit environments. Both diurnal and nocturnal insects use quite similar navigation strategies. This is despite the signal-to-noise ratio of the navigational cues being poor at low light conditions. To better understand the evolution of nocturnal life, we investigated the navigational efficiency of a nocturnal ant, Myrmecia pyriformis, at different light levels. Workers of M. pyriformis leave the nest individually in a narr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 40 publications
3
44
0
Order By: Relevance
“…It has recently been reported that UV contrast is highly effective for sky segmentation and the resulting binary panoramic skyline images can support effective navigation in ants [29,30]. The night-active M. vindex may be forced to slow down their UV receptors not only to ensure sufficient skyline contrast for landmark guidance [28], but also to obtain reliable compass information from the dim pattern of polarized skylight in the evening twilight [24].…”
Section: Discussion (A) Three Spectrally Distinct Photoreceptors In Antsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has recently been reported that UV contrast is highly effective for sky segmentation and the resulting binary panoramic skyline images can support effective navigation in ants [29,30]. The night-active M. vindex may be forced to slow down their UV receptors not only to ensure sufficient skyline contrast for landmark guidance [28], but also to obtain reliable compass information from the dim pattern of polarized skylight in the evening twilight [24].…”
Section: Discussion (A) Three Spectrally Distinct Photoreceptors In Antsmentioning
confidence: 99%
“…Ants such as the Australian desert ant Melophorus bagoti that inhabit landmark-rich environments containing grass tussocks, shrubs and trees, rely more heavily on information provided by the visual landmark panorama to find home [22,23]. Both diurnal and nocturnal bull ants of the genus Myrmecia have been shown to be guided by the landmark panorama [24,25,28] and in the case of nocturnal ants, also by the pattern of polarized skylight [24].…”
Section: Introductionmentioning
confidence: 99%
“…Because M. pyriformis rely on visual cues for orientation during their foraging excursions, using both the pattern of polarised skylight and the landmark panorama (Narendra et al, 2013c;Reid et al, 2011), we quantified the degree to which imperfect roll stabilisation affects the retrieval of navigational information (specifically heading direction) by determining the rotIDF (see Materials and methods) between a perfectly horizontally aligned reference snapshot and a current scene, which is seen through a visual system that is 'misaligned' by different degrees of roll. Ardin et al (2015) have recently conducted a similar analysis on the effects of head pitch on navigational information.…”
Section: Implications Of Imperfect Head Roll For Visual Navigationmentioning
confidence: 99%
“…Here we investigate head roll orientation in the nocturnal ant Myrmecia pyriformis Smith 1858, which has previously been shown to rely heavily on vision for navigation (Narendra et al, 2013c;Reid et al, 2011). We ask (1) whether nocturnal ants exhibit compensatory head movements to stabilise their gaze while walking, (2) to what extent their visual system is involved in head stabilisation, and (3) whether a change in ambient light intensity affects head stabilisation.…”
Section: Introductionmentioning
confidence: 99%
“…The problem with investigating the use of visual memories lies in the need to record in fine spatio-temporal detail an animal's movements, including where it directs its gaze (much like in the pioneering studies by Land and Collett [10,11] on flight control in flies), and to have knowledge of and control over the navigational information available to the animal. Until recently, this has only been possible under controlled laboratory conditions (for review, see [12]), but with the introduction of differential GPS, high-speed digital video, panoramic imagers and three-dimensional modelling tools, it has now become feasible under field conditions to precisely track the movements of navigating insects, in particular ants, and at the same time to quantify the visual information available to them [13][14][15][16].…”
Section: Introductionmentioning
confidence: 99%